Preventive Effect of Berberis Integerrima on the Serum Levels of Glucose and Lipids in Streptozotocin (STZ)-Induced Diabetes in Rats - Hossein Ashraf; Reza Heydari; Vahid Nejati; Minoo Ilkhanipoor (Fasa University of Medical Sciences, 2012)
Background and Objective: Use of medicinal plants for attenuation of hyperglycemia and restoration of lipids to normal level is clinically very important. We decided to assess the preventive role of aqueous extract of Berberis Integerrima root on the serum levels of glucose, insulin, and lipid profile in Streptozotocin (STZ)-induced diabetic rats.Materials and Methods: Forty male rats were divided into 5 groups as follows: 1- normal (N) 2- normal + barberry (N+B) (they received barberry root extract for 6 weeks) 3- diabetic (D) (they received STZ, 65 mg/kg BW /i.p.) 4- diabetic + barberry before (D+Bb) (they received barberry root extract for 3 weeks before STZ injection and continued for another three weeks) and 5- diabetic + barberry after (D+Ba) (three days after STZ injection, they received barberry root extract for 3 weeks). The experimental groups received barberry root extract (500 mg/kg bw) intra gastric by gavage for 6 weeks and the experimental period for each rat was 6 weeks.Results: Diabetic rats showed a significant increase in serum glucose, total cholesterol, triglycerides, LDL-C, and food intake as well as a decrease in HDL-C, body weight and serum insulin, compared to the other groups. Administration of the barberry root extract in diabetic rats restored these changes towards normal to some extent.Conclusion: In this study, for the first time, we showed that the administration of the barberry root extract before diabetes induction resulted in better amelioration in the serum levels of glucose, insulin, and lipid profile, compared to the group receiving it after induction: this indicates that the barberry root extract can play both a preventive and a therapeutic role in such patients.